2014
DOI: 10.5539/gjhs.v6n3p65
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with Posttraumatic Stress Disorder and Its Coping Styles in Parents of Preterm and Full-Term Infants

Abstract: Introduction:Birth of a premature infant and subsequent neonatal intensive care leads to psychological distress and trauma in parents. A large proportion of mothers show signs of trauma long after discharge from hospital. Fathers of premature infants are known to experience more stress than fathers of full-term infants. The sorrow experienced by parents of preterm infants is significantly higher than that experienced by parents of full-term infants because they have not been adequately prepared for the experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 18 publications
2
20
1
1
Order By: Relevance
“…Older maternal age was associated with higher depressive symptoms, more parenting stress, and more maternal worry about child's health. This is inconsistent with previous findings that adolescent mothers reported more parenting stress than nonadolescent mothers (Andreozzi et al, 2002) and that mothers with psychological distress were younger (Bener, 2013), although others found no relationship between depressive symptoms and maternal age (Ghorbani et al, 2014;Wei et al, 2008). In our study, the older mothers may have been more worried than younger mothers because they were more likely to have undergone infertility treatments and were worried about having a positive outcome of pregnancy.…”
Section: Differences In Mother-infant Interactions Based On Maternacontrasting
confidence: 99%
See 2 more Smart Citations
“…Older maternal age was associated with higher depressive symptoms, more parenting stress, and more maternal worry about child's health. This is inconsistent with previous findings that adolescent mothers reported more parenting stress than nonadolescent mothers (Andreozzi et al, 2002) and that mothers with psychological distress were younger (Bener, 2013), although others found no relationship between depressive symptoms and maternal age (Ghorbani et al, 2014;Wei et al, 2008). In our study, the older mothers may have been more worried than younger mothers because they were more likely to have undergone infertility treatments and were worried about having a positive outcome of pregnancy.…”
Section: Differences In Mother-infant Interactions Based On Maternacontrasting
confidence: 99%
“…Similarly, adolescent mothers have reported more parenting stress than non-adolescent mothers (Andreozzi, Flanagan, Seifer, Brunner, & Lester, 2002). However, in other studies, no relationship was seen between elevated depressive symptoms and maternal age (Ghorbani et al, 2014;Wei et al, 2008). Older mothers have also shown to have more positive motherinfant interactions than adolescent mothers, with older mothers showing more positive affect and talking more (Levine et al, 1985).…”
Section: Correlates Of Maternal Distress and Mother-infant Interactionmentioning
confidence: 93%
See 1 more Smart Citation
“…These results are in line with results of the study by Ghorbani, Dolatian, Shams, Alavi-Majd, & Tavakolian, (2014) which showed that maternal age, education, household income, and mother's job were not significantly associated with coping strategies. The correlation test was performed to uncover any correlation between variables of LBW infants' characteristics and the mean scores of mothers' coping strategies ( Table 7).…”
Section: Fig 1: Maternal Stress Level On Lbw Birthsupporting
confidence: 91%
“…Se han reportado diversas fuentes de estrés como el ambiente de la Unidad de Cuidado Intensivo Neonatal (UCIN), el comportamiento y la apariencia del bebé, el desempeño del rol paterno y la comunicación con el personal de salud (16). Los padres se sienten angustiados cuando ven los diversos tubos en el cuerpo del bebé (17) o cuando este debe recibir procedimientos invasivos (18).…”
Section: El Estrés De Los Padres En La Unidad De Cuidado Intensivo Neunclassified